2005
DOI: 10.1530/eje.1.02022
|View full text |Cite
|
Sign up to set email alerts
|

Acromegaly in a multiple endocrine neoplasia type 1 (MEN1) family with low penetrance of the disease

Abstract: Multiple endocrine neoplasia type 1 (MEN1) is an inherited syndrome that is characterised by the occurrence of tumours in the parathyroid glands, the endocrine pancreas, the pituitary gland and the adrenal glands and by neuroendocrine carcinoid tumours, often at a young age. The penetrance of MEN1 among gene carriers is reported to be high; 82-99% at age 50. We present a patient with a history of parathyroid adenomas also showing signs of acromegaly. He turned out to be a carrier of a MEN1 germ-line mutation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Concordantly, no cases of acromegaly or GH hypersecretion were diagnosed in our family or in the Finnish MEN1 families (F3-F4), and this tumor was not confirmed or clearly reported in the other very large families (F2, F5). Recently, an even lower prevalence of acromegaly (3-7.4%; 10-17% of PIT) has been reported in MEN1 (43). In addition, the nine MEN1-S reviewed here presented only 5% of cases with acromegaly (8,10,16,17,19).…”
Section: Prevalence Of Classic Men1-related Tumorsmentioning
confidence: 53%
“…Concordantly, no cases of acromegaly or GH hypersecretion were diagnosed in our family or in the Finnish MEN1 families (F3-F4), and this tumor was not confirmed or clearly reported in the other very large families (F2, F5). Recently, an even lower prevalence of acromegaly (3-7.4%; 10-17% of PIT) has been reported in MEN1 (43). In addition, the nine MEN1-S reviewed here presented only 5% of cases with acromegaly (8,10,16,17,19).…”
Section: Prevalence Of Classic Men1-related Tumorsmentioning
confidence: 53%
“…However, the actual prevalence of hypopituitarism in MEN1 is currently unknown. Somatotropinomas are relatively rare in MEN1 (14),(15) and should be differentiated from familial and isolated acromegaly/gigantism caused by other gene mutations, such as AIP (13),. Hypercortisolism occurs infrequently in MEN1 (up to 7% of cases) (14), although several studies involving large series reported no case with hypercortisolism in MEN1 (10),(36),(39),(41).…”
Section: Discussionmentioning
confidence: 99%
“…Acromegaly is an endocrine disorder which is caused in more than 95% of the cases by benign, growth hormone producing pituitary adenoma [23]. Other endocrine neoplasia such as parathyroid neoplasms can occur as part of an acromegaly-causing syndrome called multiple endocrine neoplasia (MEN) [24]. Hence, this branch involves endocrine disorders and known comorbidities.…”
Section: Resultsmentioning
confidence: 99%